Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas X.6 Farmasi SMKF IKASARI Pekanbaru - ', Nurhasanah; ', Zuhri D; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve the learning process and improve students' mathematics learning outcomes through the implementation of Problem Based Learning models. This type of research is Classroom Action Research with two cycles. The research was conducted in class X6 Farmasi SMKF IKASARI Pekanbaru in odd semester of the 2016/2017 academic year. The subject of this research were the students in the class X6 farmasi of SMKF IKASARI Pekanbaru that consist of 2 boys and 35 girls. The research instrument consists of learning tools and instruments to collect data. This study used syllabus, lesson plans and worksheets. Data collection instruments used in this study is the observation sheet and students’ test. Data analysis technique used are analysis descriptive narrative of qualitative data and descriptive statistical analysis of quantitative data. Based on the results of the study, the learning process has improved and students' mathematics learning outcomes also increased after applied Problem Based Learning models. So, Problem Based Learning models can be implemented as an alternative to learning, because learning approaches can improve the learning process and improve student learning outcomes.Keywords: Problem Based Learning models, Learning Process, Learning Outcomes.